Inovasi Manajemen Layanan Publik Dalam upaya meningkatkan investasi ekonomi di daerah (Studi Pada Pemerintah Kota Gorontalo) - Sulila, Ismet (Sam Ratulangi University, 2015)
Abstract : The innovation of public service management in increasing local economic investment. Thisresearch aims at responding the issues on the public service, particularly the licensing service to increasethe local economic investment in Gorontalo city. This research focuses on how to apply the public servicedimension on licensing in Gorontalo city, regarding two types of services; service withhighsuccessrateandservicewith alow success rate. The targeted result is to find an innovation of public service byapplying the public service dimension. The method of this research is qualitative descriptive methodthrough an in-depth and thorough study on the series of licensing service, as well as Focus GroupDiscussion (FGD) as a part of this research. The result shows that there is a new model discovered inlicensing service that would support the investor to get easy access for investment in Gorontalo city. Thisresearch is expected to contribute a positive benefit in terms of the innovation of licensing service,particularly as an effort to increase local investment and economic growth regarding the local autonomy.Keywords: Reliability, responsiveness, assurance, empathy, and tangibles.